Development of an automated ceiling fan balancing system - Ren, Dexian (Nanyang Technological University, 2024)
Electrically driven ceiling fans were invented in 1889. As they have yet to have cheaper alternatives, they are still one of the commonly used electrical appliances that circulates airflow. Despite Ceiling fans being cost-effective, if they were not dynamically balanced, they would experience vibrations, which could shorten their lifespan. As there is currently no smart solution to perform ceiling fan balancing, an automated ceiling fan balancing system was decided to be made.